Case report: A case of fulminant type 1 diabetes mellitus after COVID-19 vaccination during treatment of advanced gastric cancer: pitfall in managing immune-related adverse events - Tanaka, Toshimitsu; Nagasu, Sachiko; Furuta, Takuya; Gobaru, Mizuki; Suzuki, Hiroyuki; Shimotsuura, Yasutaka; Akiba, Jun; Nomura, Masatoshi; Fujita, Fumihiko; Kawaguchi, Takumi; Miwa, Keisuke (Frontiers in Oncology, 2023)
The occurrence of fulminant type 1 diabetes mellitus as an adverse event during cancer immunotherapy has been previously reported. However, little is known about the causal relationship between the coronavirus disease 2019 (COVID-19) vaccination and fulminant type 1 diabetes mellitus. A 60-year-old man with advanced gastric cancer, receiving S-1 + oxaliplatin and nivolumab therapy, followed by nab-paclitaxel + ramucirumab as a second-line treatment, with steroid supplementation for complications of hypopituitarism-induced hypoadrenocorticism, was administered a COVID-19 vaccine after three cycles of nab-paclitaxel + ramucirumab. Two days later, he developed severe malaise and anorexia, which required emergency admission to our hospital for suspected adrenal insufficiency. Despite increasing steroids, his general condition changed suddenly after 12 hours leading to his death. Histopathological analysis of autopsy samples revealed loss of the islets of Langerhans, indicating fulminant type 1 diabetes mellitus. We failed to recognize the onset of fulminant type 1 diabetes mellitus because its symptoms were similar to those of adrenal insufficiency. The number of reports on the onset of fulminant type 1 diabetes mellitus after COVID-19 vaccination has been increasing, and in this case, the onset occurred on the second day after COVID-19 vaccination, suggesting an association between vaccination and fulminant type 1 diabetes mellitus. Clinicians should be aware of the risk of fulminant type 1 diabetes mellitus, although rare, after COVID-19 vaccination.